Timber Transportation - A Comparative Study - Mitra, S. K.; Sood, K. G. (Indian Forester, 1980)
The cost of transporation of wood from the forests to the consuming centres is the highest component in total logging cost constituting nearly 60-70% of it, in order to find out the comparative suitability, speed behaviour and economics over various types of roads of the trucks, tractors and the traditional bullock cart, a detailed study was conducted in the teak forests on N. Betul. (Production) Division of Madhya Pradesh. The traditional bullock cart was found to be economical upto a lead of 4 kms distance on unmetalled road. It was observed that the standard of road does not have significant impact on the speed of bullock cart as evident from the break even point of 4.25 kms in tar road. Under the present working condition the efficiency of bullock cart can be increased if the improvements suggested in the paper are taken up.